2006
DOI: 10.1093/gerona/61.8.859
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength and Cognitive Decline in Older Mexican Americans

Abstract: Older Mexican Americans with reduced handgrip strength at baseline demonstrated a statistically significant decline in cognitive function over a 7-year period. By contrast, participants in the highest handgrip strength quartile maintained a higher level of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
210
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(259 citation statements)
references
References 57 publications
29
210
3
5
Order By: Relevance
“…Alfaro-Acha et al (2006) investigated the relationship between grip strength and cognitive functions (Alfaro-Acha et al 2006). They reported that as grip strength weakened, Mini Mental State Examination scores and cognitive ability decreased (Sugiura et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Alfaro-Acha et al (2006) investigated the relationship between grip strength and cognitive functions (Alfaro-Acha et al 2006). They reported that as grip strength weakened, Mini Mental State Examination scores and cognitive ability decreased (Sugiura et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, handgrip strength has been found to be associated with disability at older ages (Giampaoli et al 1999;Rantanen et al 1999;Taekema et al 2010), cognitive decline (Alfaro-Acha et al 2006), and hospitalization (Cawthon et al 2009). While there is compelling evidence that men outperform women on handgrip tests at all ages and across all continents (Bohannon et al 2006;Dodds et al 2014;Leong et al 2015), the magnitude of the male advantage appears to vary across national populations, ethnicities, and age groups.…”
Section: Sex Differences In Physical Performance Testsmentioning
confidence: 99%
“…Despite the importance of guaranteeing the reliability of a device thereby ensuring a low margin of measurement error, there is a frequent use of the hand grip dynamometer in elderly subjects with dementia, both in the clinical environment and in research [10][11][12]26 , without any prior assessment as to the reliability of its use in elderly subjects with different degrees of dementia. Therefore, this study aimed to evaluate the reliability of this measurement in this population.…”
Section: Discussionmentioning
confidence: 99%
“…One measurement that has been widely used in research and clinical practice, both in the elderly with and without dementia, is strength assessed by means of the dynamometer hand grip 4,[10][11][12] . The hand grip strength (HGS) test is a relatively inexpensive measurement that provides an approximation of overall muscle strength and which is strongly associated with functionality 4,13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation